Spontaneous monochorionic triplet pregnancy with no fetal anomaly or feto-fetal transfusion - Gandham, Sahruda (BMJ Case Rep, 2012)
We present a case of spontaneously conceived monochorionic triamniotic triplet pregnancy with no fetal anomaly or feto-fetal transfusion. The mother developed gestational diabetes at 20 weeks gestation, and at 20 weeks and 4 days gestation triplet 2 was found to have selective growth restriction and absent end diastolic flow. Although laser treatment and clamping of the umbilical cord of the growth-restricted baby was considered, the management was conservative with regular ultrasound scans and antenatal corticosteroids at 24 weeks gestation, and the umbilical artery Doppler reverted to normal at 26 weeks and 4 days and growth velocity was maintained. An elective caesarean section was performed at 33 weeks gestation to deliver three boys in excellent condition who only required feeding support.